APPLESOSS: A Producer of ProfiLEs for SOSS. Application to the NIRISS SOSS Mode. (1st October 2022) - Radica, Michael; Albert, Loïc; Taylor, Jake; Lafrenière, David; Coulombe, Louis-Philippe; Darveau-Bernier, Antoine; Doyon, René; Cook, Neil; Cowan, Nicolas; Espinoza, Néstor; Johnstone, Doug; Kaltenegger, Lisa; et al.
Abstract: The SOSS mode of the Near Infrared Imager and Slitless Spectrograph instrument is poised to be one of the workhorse modes for exoplanet atmosphere observations with the newly launched James Webb Space Telescope (JWST). One of the challenges of the SOSS mode, however, is the physical overlap of the first two diffraction orders of the G700XD grism on the detector. Recently, the ATOCA algorithm was developed and implemented as an option in the official JWST pipeline, as a method to extract SOSS spectra by decontaminating the detector—that is, separating the first and second orders. Here, we present A Producer of ProfiLEs for SOSS (APPLESOSS), which generates the spatial profiles for each diffraction order upon which ATOCA relies. We validate APPLESOSS using simulated SOSS time series observations of WASP-52 b, and compare it to ATOCA extractions using two other spatial profiles (a best and worst case scenario on-sky), as well as a simple box extraction performed without taking into account the order contamination. We demonstrate that APPLESOSS profiles retain a high degree of fidelity to the true underlying spatial profiles, and therefore yield accurate extracted spectra. We further confirm that the effects of the order contamination for relative measurements (e.g., exoplanet transmission or emission observations) is small—the transmission spectrum obtained from each of our four tests, including the contaminated box extraction, is consistent at the ∼1 σ level with the atmosphere model input into our noiseless simulations. We further confirm via a retrieval analysis that the atmosphere parameters (metallicity and C/O) obtained from each transmission spectrum are consistent with the true underlying values.